The Responsibility of the Heirs of the Magistratus Municipales. Examples from the Field of Datio Tutoris by the Magistrates - Emese Újvári (Journal on European History of Law, 2023)
In the Roman Empire during the imperial period, in certain cases it was possible to take action against the magistratus municipales who had committed an omission or error in the guardianship order, if the default had (indirectly) caused damage to the ward. The sources suggest that the action which could be brought in such cases, the actio subsidiaria, was an actio poenalis and could not originally be brought against the heirs of the magistratus in the event of his death. Later, however, the heirs of the magistratus could also be sued under certain conditions, in order to provide greater protection for the interests of the ward.